Promoting Agri-Food Sector Transformation in Bangladesh : Policy and Investment Priorities - World Bank (World Bank, Washington, DC, 2020)
The agriculture sector has been critically important in reducing poverty in Bangladesh, and further progress in agriculture will remain important as Bangladesh’s economy continues to evolve. Declining agricultural productivity growth poses substantial risk to the development of the rural economy. There are substantial market opportunities for productive diversification and increased value addition for the agri-food sector in Bangladesh. The agri-food ecosystem analysis carried out for this study identifies critical constraints to the diversification and modernization of the agri-food sector. The Covid-19 (Coronavirus) crisis has hit Bangladesh’s economy and its agri-food sector hard and lasting impacts can be expected on the sector. The overall aim of this report is to identify policy and public investment opportunities for increasing agricultural diversification and creating an enabling business environment for private sector investment along the agri-food supply chain using the maximizing finance for development (MFD) framework. The report is intended to provide guidance to the Government of Bangladesh (GoB) to implement and operationalize the strategic priorities of agricultural diversification and commercialization, as outlined in national agricultural policy 2018, to improve farms’ incomes, create rural jobs, and attain nutrition security in the country. The report is also intended to inform the World Bank’s strategies and dialogue for agriculture and rural development in Bangladesh and sharpen priorities for future engagement on agri-food sector modernization initiatives.